2007
DOI: 10.4049/jimmunol.179.9.5990
|View full text |Cite
|
Sign up to set email alerts
|

Jagged1 and Delta1 Differentially Regulate the Outcome of Experimental Autoimmune Encephalomyelitis

Abstract: Notch signaling plays an important role during T cell development in the thymus and in T cell activation but the role of Notch in autoimmunity is not clear. We investigated the role of Jagged1 and Delta1 in experimental autoimmune encephalomyelitis. During experimental autoimmune encephalomyelitis, Delta1 expression is up-regulated on dendritic cells and B cells after priming while Jagged1 is up-regulated only on dendritic cells. Administration of anti-Jagged1 Ab exacerbated clinical disease while that of anti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
113
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 95 publications
(116 citation statements)
references
References 47 publications
3
113
0
Order By: Relevance
“…Neutralization of DLL4 during the induction of EAE resulted in an increase in the number of peripherally induced T Reg cells with a corresponding decrease in disease severity 91 . The effect was specific to DLL4, as DLL1 blockade had no effect on T H 17 and T Reg cell differentiation during EAE 92 . In addition, a more recent study showed that anti-DLL4 treatment prevented the development of, and even reverted, type 1 diabetes in nonobese diabetic (NOD) mice by inducing an increase in the number of DC-dependent de novo thymic T Reg cells 93 .…”
Section: The Impact Of Notch On Other T H Cell Subsets In Vivomentioning
confidence: 90%
“…Neutralization of DLL4 during the induction of EAE resulted in an increase in the number of peripherally induced T Reg cells with a corresponding decrease in disease severity 91 . The effect was specific to DLL4, as DLL1 blockade had no effect on T H 17 and T Reg cell differentiation during EAE 92 . In addition, a more recent study showed that anti-DLL4 treatment prevented the development of, and even reverted, type 1 diabetes in nonobese diabetic (NOD) mice by inducing an increase in the number of DC-dependent de novo thymic T Reg cells 93 .…”
Section: The Impact Of Notch On Other T H Cell Subsets In Vivomentioning
confidence: 90%
“…The effect of Notch signaling manipulation on the course of autoimmune inflammatory diseases has been examined. In a recent study, treatment with Jagged1-and Delta1-Fc fusion proteins differentially modulated the course of EAE (27). With ␥-secretase inhibitors, it has been shown that blocking the Notch pathway prevents Th1 polarization and IFN-␥ secretion (15).…”
Section: Discussionmentioning
confidence: 99%
“…The hybridoma cells were prepared as described above, and antibodies that reacted with mouse Notch2-transfected CHO cells, but not with untransfected CHO cells, were screened and cloned. All these mAbs were purified from ascites produced in pristan-primed ICR nude mice by the caprylic acid and ammonium sulphate precipitation method [36][37][38][39] . Two hundred and fifty micrograms of HMJ1-29 or control hamster IgG (UC8-1B9) and 100 mg of HMN1-12 or HMN2-29 were injected intraperitoneally on the indicated days.…”
Section: Methodsmentioning
confidence: 99%